May Measurement Month 2017 blood pressure screening: findings from Malaysia—South-East Asia and Australasia. (24th April 2019) - Chia, Yook-Chin; Ching, Siew Mooi; Chew, Bee Nah; Devaraj, Navin Kumar; Siti Suhaila, Mohd Yusof; Tay, Chai Lee; Kang, Pei San; Verna Lee, Kar Mun; Kong, Sie Zing; Teoh, See Wie; Nurjasmine, Aida Jamani; Poulter, Neil R; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. However there are still many individuals, particularly in many countries in Asia, who have poor BP control. In Malaysia, less than two-fifths have achieved BP control. We participated in BP screening in Malaysia in conjunction with the May Measurement Month 2017 (MMM17), a global initiative by the International Society of Hypertension (ISH) aimed at screening more individuals for earlier detection of hypertension. A nationwide screening of adults aged ≥18 was carried out through health campaigns at clinics, hospitals, during family day events, and charity runs from 1 April 2017 to 31 May 2017 in 42 centres. We used the detailed protocol provided by ISH for data collection. A total of 4116 individuals were screened during MMM17. After multiple imputation, 32.4% ( n = 1317/4059) had hypertension. Out of this, 63.9% (842/1317) of those with hypertension were on treatment. Of individuals receiving antihypertensive medication with an imputed BP, 59.5% ( n = 496/834) of them had controlled BP. MMM17 was the largest organized BP screening campaign undertaken by health professionals in Malaysia. This study identified that 32.4% of screened individuals had hypertension and 59.5% individuals with treated hypertension had achieved BP control.